2023
DOI: 10.1002/ldr.4564
|View full text |Cite
|
Sign up to set email alerts
|

Soil salinity estimation: Effects of microwave dielectric spectroscopy and important frequencies

Abstract: The microwave dielectric constant is a key bridge in establishing the relationship between microwave remote sensing and soil salinity (electrical conductivity, EC). However, the response between microwave dielectric spectrum type, frequency, and soil salinity is still unclear. The purpose of this study is to reveal the dielectric spectrum and frequency range closely related to soil salinity. In this study, 129 surface soil samples were collected, and soil EC and microwave dielectric spectrum (frequency range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…The diameter of the capacitor covers was 2 cm, the distance between them was 0.7 cm. The soil for the study was used in an air-dry state to level out the effects of moisture, the content of which has a significant effect on the dielectric constant (Zhao et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…The diameter of the capacitor covers was 2 cm, the distance between them was 0.7 cm. The soil for the study was used in an air-dry state to level out the effects of moisture, the content of which has a significant effect on the dielectric constant (Zhao et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…A et al 4 found that the content of soil Na and Cl was significantly correlated with the spectral reflectance of 510.98 nm [23]. Srivastava et al believe that the spectrum in the range of 1390 to 2400nm is closely related to soil salinity changes [24]. Peng et al analyzed the spectral response characteristics under different salinization conditions and pointed out that the mid-infrared spectroscopy has a high accuracy in estimating the contents of Mg, Na, and Cl, but has a general effect in estimating the contents of Ca and SO [25].…”
Section: Background and Motivationmentioning
confidence: 99%
“…Then, all the samples were dried in an oven (80 ℃) for 36 h and weighed, and the dry weight was recorded. The 154 samples were randomly divided into two groups: one was a modeling sample (70%), which was used to establish a spring wheat leaf moisture content prediction model; the other was a verification sample (30%), which was used to verify the established estimation model [36]. The leaf water content was calculated according to formula (1).…”
Section: Field Data Collection and Lwc Determinationmentioning
confidence: 99%